Identifying Student Misconceptions Using Three-Tier Test with Certainty of Response Index on Temperature and Heat Topics - Oktavia, Popy; Suhadi, Suhadi; Widya, Herma; Putri, Jamiatul Khairunnisa; Mabruroh, Faizatul (Universitas Islam Negeri (UIN) Mataram, 2024)
This research aims to identify students' misconceptions using a Three-Tier diagnostic test assisted by the Certainty of Response Index (CRI) on temperature and heat material. The data analysis method used in this research is quantitative descriptive and equipped with a three-tier Certainty of Response Index (CRI). The population in this study was class XI 1 IPA MAN 1 Musi Banyuasin with 30 students, and the sample in this study was class. Data collection techniques were used during the observation, test, and documentation stages. The research results showed that the misconceptions identified regarding the concept of temperature and heat were 40%, 36% understood the concept, 6% understood the concept but needed clarification and 18% needed to learn the concept. The misconceptions experienced by students are classified as moderate-level misconceptions with a percentage range of 31% ≥ 60%. The cause of misconceptions is the students' errors in learning context and incomplete reasoning. It is hoped that the results of this research can provide information about misconceptions that occur in the matter of temperature and heat and can serve as a guide for further research to find out the causes of misconceptions and efforts to overcome them.